Sensory Evaluation of Rice Grain: Methods, Applications, and Significance in Experimental Research (Plant Bulletin, 2025)
Sensory evaluation is a dynamic tool for evaluating the organoleptic potentials of rice i.e., appearance, aroma, taste, and texture which are significant to consumer acceptance and marketability. This review consolidates current methodologies for sensory scoring of rice, including both human panel assessments and instrumental techniques (GC, Electronic nose, TPA, AI). Panelist training, standardized evaluation protocols, and the integration of sensory data into rice breeding and quality control programs may include. By examining global practices and the review underlines the sensory profiling in the variety approval process and highlights its role in developing rice cultivars that align with both agronomic performance and market expectations.
Keywords: Aroma; Basmati; sensory; KOH; Chromatography; texture